Nanotechnology in Oil and Gas Industries Principles and Applications (Topics in Mining, Metallurgy and Materials Engineering,, 2018)
This book provides a powerful source to develop new, rapid and highly efficient materials for the application in various fields of oil and gas fields. It focuses on the synthesis, characterization and applications of various Nanomaterials, presenting the state-of-the-art in developments and innovations in nanocomposites. This book provides the complete practical and theoretical information about the synthesis of nanoparticles with potential use in the field of oil and gas.